Comparison of analgesia provided by lidocaine, lidocaine-morphine or lidocaine-tramadol delivered epidurally in dogs following orchiectomy - Almeida, Ricardo M.; Escobar, André [UNESP]; Maguilnik, Samara (Wiley-Blackwell, 2010)
ObjectiveTo evaluate and compare the postoperative analgesia provided by epidural lidocaine, lidocaine/morphine or lidocaine/tramadol in dogs following elective orchiectomy.Study designProspective experimental trial.AnimalsThirty-six mongrel dogs aged 2-8 years old, weighing 6.6-22 kg.MethodsThe dogs received 6.0 mg kg-1 of lidocaine combined with 1.0 mg kg-1 of tramadol, 0.1 mg kg-1 of morphine or 0.01 mL kg-1 of 0.9% NaCl epidurally. Analgesia was assessed at 4, 8, 12, 18 and 24 hours (T4, T8, T12 and T24) after the offset of lidocaine using a scale composed of physiologic and behavioral parameters. Rescue analgesia with morphine (0.2 mg kg-1, IM) was performed if the evaluation score exceeded 10 during the postoperative period. The scores over time were analyzed using the Friedman's two-way analysis of variance and the comparison between groups was made by the Kruskal-Wallis test with statistical significances accepted if p < 0.05.ResultsThere were no differences in the pain scores between the morphine and tramadol groups over time and no rescue analgesia was administered. In the NaCl group, rescue analgesia was needed at T4, T8 and T12. Within this group, the final evaluation times (T18 and T24) had lower pain scores than at T4, T8 and T12.Conclusions and clinical relevanceEpidural lidocaine/tramadol provided an analgesic effect comparable to that of epidural lidocaine/morphine during the first 12 hours after surgical castration without substantial side effects, suggesting that tramadol may be an effective postoperative analgesic in dogs submitted to this surgical procedure.
Keywords: analgesia; Dog; epidural; morphine; Orchiectomy; Tramadol